Practical possibilities of ecological education in the context of „Nature explorers" programme - Latawiec, Michał (Studia Ecologiae et Bioethicae, 2008)
The aim of this article is to introduce ecological education in practicaluse. Many expectations are connected with in formal education, these expectations are often met by organizing educational actions, the article describes an educational programme called “Nature explorers”, which was realized by Wilanów Palace Museum in cooperation with University of Cardinal Stefan Wyszyński in Warsaw, the article also presents conclusions and opinion about possibilities of accomplish the tasks that are set before ecological education after carrying the educational programme.